The Effect Of Network Learning On Students' Learning Motivation During The Covid-19 Pandemic At UPTD SDN 146 Barru Mallusetasi District, Barru Regency (International Journal of Elementary School Teacher, 2022)
This research was conducted at UPTD SDN 146 Barru, Mallusetasi District, Barru Regency which has a problem formulation, namely: 1) What is the picture of online learning at UPTD SDN 146 Barru during the covid-19 pandemic? 2) What is the picture of student learning motivation at UPTD SDN 146 Barru during the covid-19 pandemic? 3) Is there any effect of online learning on students' learning motivation during the covid-19 pandemic at UPTD SDN 146 Barru? Therefore, this study aims: 1) To find out the description of online learning for UPTD SDN 146 Barru students during the covid-19 pandemic. 2) To find out the description of student learning motivation at UPTD SDN 146 Barru during the covid-19 pandemic. 3) To find out whether there is an effect of online learning on students' learning motivation during the covid-19 pandemic at UPTD SDN 146 Barru. This type of research is a quantitative correlational model. The data collection method uses a questionnaire and documentation, which has a population of 61 students, with a sampling technique using a saturated sampling technique. The data analysis technique used descriptive analysis and inferential analysis using simple linear regression analysis techniques. The results of the analysis show that the significance value of online learning and student learning motivation can be seen from Fcount which is greater than Ftable, so that there is a significant effect. Then the value of sig. smaller than the level of significance. These results can be concluded that there is a significant influence between online learning on students' learning motivation during the covid-19 pandemic at UPTD SDN 146 Barru, Mallusetasi District, Barru Regency. The data collection method uses a questionnaire and documentation, which has a population of 61 students, with a sampling technique using a saturated sampling technique. The data analysis technique used descriptive analysis and inferential analysis using simple linear regression analysis techniques. The results of the analysis show that the significance value of online learning and student learning motivation can be seen from Fcount which is greater than Ftable, so that there is a significant effect. Then the value of sig. smaller than the level of significance. These results can be concluded that there is a significant influence between online learning on students' learning motivation during the covid-19 pandemic at UPTD SDN 146 Barru, Mallusetasi District, Barru Regency.